Question and answer
The following system of equations is _____. y = -1/3x + 2/3 2x + 6y = 4
Question
Asked 5/7/2015 5:41:04 PM
Updated 5/8/2015 3:00:00 AM
4 Answers/Comments
This conversation has been flagged as incorrect.
Flagged by yeswey [5/8/2015 3:00:00 AM]
s
Get an answer
Original conversation
User: The following system of equations is _____. y = -1/3x + 2/3 2x + 6y = 4

Weegy: The following system of equations is A. independent
biank1989|Points 238|

User: Solve the following system by graphing. x - y = 4 x + y = 2 What is the solution of the system?

Weegy: The solution set of (3x - 1)^2 = 5 is x = x = (5^1/2)/3 + 1/3 .
(3x - 1)^2 = 5
3x - 1 = 5^1/2
3x = 5^1/2 + 1
x = (5^1/2)/3 + 1/3



User: Solve the following system by graphing. x + y - 6 = 0 x - y = 0 What is the solution of the system?

User: y = 2x + 3 2y = 4x + 6 The system of equations has _____ solution(s).

User: For the following system, use the second equation to make a substitution for y in the first equation. 2x + y = 6 y = 3x + 4 What is the resulting equation?

User: For the following system, use the second equation to make a substitution for y in the first equation. 3x + y = 1 y + 4 = 5x What is the resulting equation?

User: For the following system, use the second equation to make a substitution for x in the first equation. x + 5y - 10 = 0 x = 2y - 8 What is the resulting equation in simplest form?

Question
Asked 5/7/2015 5:41:04 PM
Updated 5/8/2015 3:00:00 AM
4 Answers/Comments
This conversation has been flagged as incorrect.
Flagged by yeswey [5/8/2015 3:00:00 AM]
New answers
Rating
3
x - y = 4
x + y = 2
adding up equations the result is 2x = 6
x = 6/2 = 3
3 - y = 4
y = 3 - 4 = -1
the solution for the system x - y = 4 x + y = 2 is (3, -1)
Added 5/8/2015 2:54:53 AM
This answer has been confirmed as correct and helpful.
Confirmed by sujaysen [5/8/2015 10:21:08 AM]
3
y = 2x + 3
2y = 4x + 6
substitute y in the second equation the result is:
2(2x + 3) = 4x + 6
4x + 6 = 4x + 6
4x - 4x = 6 - 6
0 = 0
the system of equations y = 2x + 3 2y = 4x + 6 has infinite solutions.
Added 5/8/2015 2:56:06 AM
This answer has been confirmed as correct and helpful.
Confirmed by sujaysen [5/8/2015 10:23:40 AM]
3
For the system 3x + y = 1 y + 4 = 5x, use the second equation to make a substitution for y in the first equation, the resulting equation is 3x + (5x - 4) = 1.
Added 5/8/2015 2:58:26 AM
This answer has been confirmed as correct and helpful.
3
For the following system, x + 5y - 10 = 0 x = 2y - 8, use the second equation to make a substitution for x in the first equation. The resulting equation is: 2y - 8 + 5y - 10 = 0, it is 7y - 18 = 0 in simplest form.
Added 5/8/2015 2:59:53 AM
This answer has been confirmed as correct and helpful.
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
x + y = 0 x - y + 2 = 0 User: Solve the following system of equations graphically. y - 4 = 0 2x - y - 2 = 0 What is the solution set?
Weegy: |2x - 5| = 4 2x - 5 = -4 or 2x - 5 = 4 2x - 5 = -4; 2x = -4 + 5; 2x = 1; x = 1/2; 2x - 5 = 4; 2x = 4 + 5; 2x = 9; x = 9/2; x = 1/2 or x = 9/2 User: Given the following system of equations, identify the type of system. x + y = 4 x - y = 6 User: Given the following system of equations, identify the type of system. y = -x + 4 2x + 2y = 8 Weegy: The answer is A.independent. User: Which of the following points is a solution of the system shown? x + y 6 x 4 (More)
Question
Updated 5/14/2015 3:05:31 AM
4 Answers/Comments
x + y = 0
x - y + 2 = 0
adding up equations the result is:
2x + 2 = 0
2x = -2
x = -2/2 = -1
y = -x = -(-1) = 1
The solution for the system x + y = 0 x - y + 2 = 0 is (-1, 1)
Added 5/14/2015 3:02:14 AM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [5/14/2015 5:15:16 AM]
y - 4 = 0
y = 4;
2x - (4) - 2 = 0
2x = 6
x = 6/2 = 3
the solution for the system y - 4 = 0 2x - y - 2 = 0 is (3, 4)
Added 5/14/2015 3:03:27 AM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [5/14/2015 5:15:26 AM]
x + y = 4
x - y = 6
adding up equations the result is 2x = 10
x = 10/2 = 5
5 + y = 4
y = 4 - 5 = -1
the solution for the system x + y = 4 x - y = 6 is (5, -1)
Added 5/14/2015 3:05:31 AM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [5/14/2015 5:15:36 AM]
31,981,771
questions answered
GET
Answers.
GET THE APP.
weegy*
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
Heterosexual meaning
7/29/2020 5:45:01 AM| 6 Answers
The most common age for shaken baby syndrome
7/30/2020 7:52:13 PM| 5 Answers
excretion rates of drugs vary greatly depending upon what
Weegy: Excretion rates of drugs vary greatly depending upon the type of drug involved and medical condition of the ...
8/1/2020 1:36:06 AM| 3 Answers
The NIMS Management Characteristic of Chain of Command and Unity of ...
Weegy: The National Incident Management System (NIMS) is a standardized approach to incident management developed by ...
7/30/2020 3:11:05 PM| 2 Answers
S
L
Points 352 [Total 3349] Ratings 1 Comments 342 Invitations 0 Online
S
L
P
L
P
Points 242 [Total 6265] Ratings 0 Comments 242 Invitations 0 Offline
S
L
P
R
P
R
L
P
P
C
R
P
R
L
P
R
Points 238 [Total 12329] Ratings 1 Comments 228 Invitations 0 Online
S
L
P
1
Points 210 [Total 3066] Ratings 1 Comments 200 Invitations 0 Offline
S
L
Points 202 [Total 1695] Ratings 1 Comments 192 Invitations 0 Offline
S
L
Points 154 [Total 4539] Ratings 1 Comments 144 Invitations 0 Offline
S
Points 89 [Total 89] Ratings 0 Comments 89 Invitations 0 Offline
S
L
1
Points 86 [Total 3397] Ratings 1 Comments 76 Invitations 0 Offline
S
L
Points 71 [Total 230] Ratings 0 Comments 71 Invitations 0 Offline
S
L
L
Points 23 [Total 5311] Ratings 0 Comments 23 Invitations 0 Online
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.